2016
DOI: 10.1021/acs.jnatprod.6b00796
|View full text |Cite
|
Sign up to set email alerts
|

Polycycloiridals with a Cyclopentane Ring from Iris tectorum

Abstract: Six new iridal-type triterpenoids containing an unprecedented cyclopentane ring, polycycloiridals E-J (1-6), were isolated from a large-scale re-extraction of Iris tectorum. A possible biosynthesis pathway is postulated. The known spirioiridotectal D (7) was also obtained in the current investigation, and its structure was unequivocally defined using X-ray diffraction data. Compound 7 suppressed LPS-activated NO production in the BV2 cell line with an IC value of 0.54 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, these compounds contain two E configured double bonds at Δ 14(15) and Δ 16(17) . 27 Li et al 22 reported five tricyclic iridal-type triterpenoid analogs bearing the 6/5/7-core named polycycloiridals K–O ( 60–64 ) from Belamcanda chinensis and these metabolites possess a cyclopentane core resulting via cyclization between C-18 and C-22 of the homofarnesyl chain. Moreover, these compounds illustrated weak PTP1B inhibitory effects.…”
Section: Iridal Triterpenesmentioning
confidence: 99%
“…Furthermore, these compounds contain two E configured double bonds at Δ 14(15) and Δ 16(17) . 27 Li et al 22 reported five tricyclic iridal-type triterpenoid analogs bearing the 6/5/7-core named polycycloiridals K–O ( 60–64 ) from Belamcanda chinensis and these metabolites possess a cyclopentane core resulting via cyclization between C-18 and C-22 of the homofarnesyl chain. Moreover, these compounds illustrated weak PTP1B inhibitory effects.…”
Section: Iridal Triterpenesmentioning
confidence: 99%
“…Previous chemical investigations have indicated that I. tectorum Maxim. contains a range of compounds including isoflavones, 2 C ‐glycosylflavone, 3 iridal‐type triterpenoids, 4–10 lignans 11 and apocynin derivatives 12 . In addition, an HPLC‐DAD/ESI‐MS n analysis used both positive and negative ion modes to identify fourteen known flavonoids and three phenolic acids in the rhizome of I. tectorum 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In the past, natural product chemists used to rely on polarimetry to draw conclusions about either enantiomeric purity or AC of isolated chiral secondary metabolites [ 27 ]. Even today, however, it is not unusual to find stereochemical assignments based on comparisons of chiroptical properties (optical rotation, sometimes measured in different conditions, and/or ECD) for structurally correlated compounds [ 28 , 29 , 30 ], or even based on biosynthetic considerations [ 31 , 32 ]. It is important to mention that herein we are not questioning the referenced assignments, but rather highlighting practices that may result in misassignments.…”
Section: Introductionmentioning
confidence: 99%